Towards The Development Of Financial Inclusion Index Using Islamic Finance Approach: Malaysia's Setting - Junaidah Abu Seman; Nurul Nazlia Jamil; Azreen Jihan Che Mohd Hashim (Asian Scholars Network, 2024)
The aimsof the study are to examine data availability and develop a conceptual framework for the computation of an integrated Islamic finance-based index of financial inclusion in Malaysia.In determining the level of financial inclusion, systematic indicators are inconclusiveparticularlyon its measurement based onIslamic finance.This study employs a self-administered questionnaire and secondary data from two important institutions in Malaysia which administer zakat and waqf. It is found that, although the wealth distribution indicators i.e., zakatand waqfare available for the index’s data source, the data thatcould be used to ratefinancial inclusion usingIslamic finance approach are still incomplete and limited.It is hoped that the findings on data availability and suggested conceptual framework would be useful for the development of Islamic finance-based index of financial inclusion.